2018
DOI: 10.20882/adicciones.965
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de la intervención Motivacional y la Terapia Cognitivo-conductual para el tratamiento del Juego Patológico

Abstract: ResumenAbstract original adicciones vol. xx, nº x ·

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
(14 reference statements)
0
8
0
2
Order By: Relevance
“…For example, childhood abuse persistently increased amygdala activation and reduced prefrontal cortical control over amygdalar responses (Teicher et al, 2003) and is well documented to predispose individuals to drug addiction (Choi et al, 2017). Furthermore, effective psychological interventions for obesity and gambling disorder have been reported to reduce negative urgency (Delgado-Rico et al, 2012; Garcia-Caballero et al, 2018).…”
Section: Neurocircuitry Implicated In Negative Urgency and Addictionmentioning
confidence: 99%
“…For example, childhood abuse persistently increased amygdala activation and reduced prefrontal cortical control over amygdalar responses (Teicher et al, 2003) and is well documented to predispose individuals to drug addiction (Choi et al, 2017). Furthermore, effective psychological interventions for obesity and gambling disorder have been reported to reduce negative urgency (Delgado-Rico et al, 2012; Garcia-Caballero et al, 2018).…”
Section: Neurocircuitry Implicated In Negative Urgency and Addictionmentioning
confidence: 99%
“…All psychological interventions have globally been shown to be effective in reducing gambling symptoms compared with no treatment or waitlist control conditions [13,14]. With respect to the specific therapeutic methods, studies have shown that the best efficacy is achieved with a cognitivebehavioral approach [5,7,8,11,15,16], as well as with interventions using motivational interviewing techniques [15][16][17][18][19].…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…CBT is the most frequently used, most researched, and empirically proven successful psychotherapeutic intervention for gambling disorder [4,5,7,[9][10][11]15,16,20]. The advantages of CBT are that it is a well structured therapeutic approach, limited in time, more economically viable than some other therapeutic interventions, with long-term positive effects and lower risks of relapse during the followup period [21][22][23].…”
Section: Cognitive-behavioral Therapymentioning
confidence: 99%
“…Los datos presentados van en línea con la literatura existente hasta la fecha: diferencias de género en la búsqueda de tratamiento, donde sólo 1 de cada 10 serían mujeres, a pesar de que en los estudios en población general la relación sea de 1:3 [19]; menor riesgo de desarrollar problemas con el juego asociado a estar casado o tener una relación estable [20]; tiempo de evolución media del problema con el juego en torno a 3 años en hombres y 12 años en mujeres [21,22]; presencia de deudas así como elevada cantidad de las mismas, sobre todo en jugadores online [23]; también se observaron elevados niveles de impulsividad, tradicionalmente asociados a los jugadores en comparación con población normal [24,25], actuarían también como predictores del abandono del tratamiento en este tipo de pacientes [25]. Sin embargo, su principal actividad de juego, ya no son las máquinas tragaperras, que tradicionalmente habían estado detrás de más del 80% de los casos de juego patológico [17], sino las apuestas deportivas.…”
Section: Dos O Más Juegosunclassified